Batch adsorption and process optimization for sequestration of Cr(VI) from aqueous solution using biofilm forming filamentous fungus Aspergillus niger BSC-1. (December 2022) - Chatterjee, Shreosi; Mahanty, Shouvik; Das, Papita; Chaudhuri, Punarbasu; Das, Surajit
Abstract: Chromium (Cr) contamination in an aquatic environment is one of the greatest concerns nowadays. However, biosorption by various microorganisms is proven to be an environmentally sustainable method. The present study investigated fungal biofilm-mediated sorption of hexavalent chromium [Cr(VI)] using manglicolous filamentous fungus Aspergillus niger BSC-1 obtained from the Indian Sundarban mangrove ecosystem. Biosorbents, such as fungal pellet and fungal biofilm, were utilized for Cr(VI) sequestration. The result showed significantly higher removal of Cr(VI) by fungal biofilm (97.81 ± 2.5 %) than the fungal pellet (79.14 ± 2.4 %) ( P  < 0.05; two-way ANOVA). Batch adsorption study showed that the highest removal efficiency was attained at 40 °C and pH 3 with 3 g/L of fungal biofilm. The adsorption isotherms, kinetics and thermodynamic analysis suggested monolayer, endothermic and chemisorption of Cr(VI) on the fungal biofilm biosorbent. The adsorption process was further optimized using response surface methodology (RSM) - Central Composite Design (CCD), suggesting the quadratic model for Cr adsorption with high significance ( P  < 0.0001). The 3D surface plots among the three key variables, i.e., pH, temperature and Cr concentration, revealed that maximum sequestration (92.39 %) was achieved at 40 °C, pH 3 and 30 mg/L of Cr(VI) using 3 g/L of fungal biofilm. Regeneration study demonstrated that fungal biofilm retained 87.19 ± 3.23 % of Cr(VI) sorption with no significant reduction in Cr(VI) removal after five successive adsorption-desorption cycles. X-ray photoelectron spectroscopic analysis showed that adsorption, reduction and complexation mechanisms were involved in Cr(VI) detoxification. Furthermore, the fungal biofilm biosorbent efficiently removed approximately 100 % of Cr(VI) from leather effluent within 90 min of reaction time. Graphical abstract: Unlabelled Image Highlights: Biofilm of Aspergillus niger BSC-1 efficiently removed Cr(VI) from aqueous solution. Adsorption models revealed monolayer, endothermic and chemisorption of Cr(VI) on fungal biofilm. The quadratic model predicted from response surface methodology optimized biosorption of Cr(VI). Fungal biofilm retained 87.19 % of adsorption efficiency up to five adsorption-desorption cycles. Sequestration of Cr(VI) was mediated via adsorption, reduction and complexation mechanisms.